Building the technological European Community through education: European mobility and training programmes in the 1980s. (May 2021) - Flury, Carmen; Geiss, Michael; Guerrero Cantarell, Rosalía
The Community Action Programme for Education and Training for Technology (COMETT) played a key role in paving the way for increased cooperation between the member states of the European Community (EC) in the field of education and in the promotion of intra-Europe mobility. In this article, COMETT is considered as a non-traditional education and training programme for solving economic challenges in the context of technological change that was focused on the training of a highly skilled workforce. The process of setting the agenda for COMETT is studied through an analysis of official EC policy documents and archival material from the EU's historical archives in Florence. Our analysis suggests that the challenge posed by new information technologies acted as a catalyst for a new approach to education governance that was based on closer cooperation between European universities and industry. Promoting intra-Europe mobility among highly skilled workers and students was a key part of the programme, which defined an economic and social strategy for Europe in response to technological change. Educational and social goals were secondary in the design and implementation of the COMETT programme, which, first and foremost, was motivated by the EC agenda to boost the competitiveness of European industry.